LYNCHNING: EN SVØBE FOR MENNESKEHEDEN - Stepputat, Finn (Tidsskriftet Antropologi, 2002)
The article explores the phenomenon of mob violence in predominatly Mayan towns in rural Guatemala. Since 1996, more than 100 people have been killed by crowds in rural towns. The victims have usually been young men accused of often minor criminal acts, or representatives of the state trying to protect the victims. The occurrence of mob violence coincides roughly with the area where the army organized civil self-defence patrols during the civil war from 1981-96 as part of the national security counterinsurgency program. The post-conflict transition has paradoxically brought security back to the top of the political agenda as political violence has been substituted and overshadowed by violence related to drug trafficking and other forms of criminality. The article shows how mob violence has been interpreted in the context of postconflict transformations where the elimination of violence and violent conflicts has been addressed as an object of development, and suggests that we, in addition to common sociological interpretations, may understand lynchings as an exclusive practice of communal sovereignty within a transnational political field of politics of in/security.